The Relationship Between Self-Evaluation, Feasibility and Effective Career Planning Among College Student in China - Wang, Jiajing (2008)
The main objective of this study is to examine the relationship between self-evaluation, feasibility and effective career planning among college students in China. The two dimensions which namely self-evaluation and feasibility (independent variables) will be used to measure effective career planning (dependent variables). Beside this study will also try to find out which factor is more important in effective career planning. In order to attain the objectives, this study will be conducted quantitatively where data will be collected through distribution of questionnaires to 200 college students randomly in a college of China. 192 of returned and usable questionnaires are expected to be used for analysis. The data will be analyses using Person Correlation to study the relationships between independent variable and dependent variables and also through Reliability Test and Descriptive Analyses. The findings indicated that there were relationships between self-evaluation, feasibility and effective career planning. Further, the findings also revealed that establishment goal is the most important factor contributed to the effective career planning. In conclusion, the study shows that self-evaluation and feasibility being positively correlated to effective career planning.